Q: Is it true when the term AB mean to multiply A by B?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(a-b)2 = (a-b)(a-b). You have to multiply each term in the left monomial by each term in the right monomial: a2 - ab - ab + b2 = a2 - 2ab + b2.

When applying distributive property to solve an equation, you multiply each term by term. For instance: a(b + c) = ab + ac

It is an expression and a term that are of equal value

Steps in getting the square of trinomial: 1. Square the first term. 2. Square the second term. 3. Square the last term. 4. Multiply the first and second term, then, square them. 5. Multiply the second and third term, then, square them. 6. Lastly, multiply the first and last term, then, square them. Examples: (a+b+c)^2 1st step: a^2 2nd step: b^2 3rd step: c^2 4th step: ab^2 5th step: bc^2 6th step: ac^2 Then the answer will be, a^2+b^2+c^2+ab^2+bc^2+ac^2. Hope this will help you in your assignment!

b*ab = ab2 Suppose b*ab = ab + b2. Assume a and b are non-zero integers. Then ab2 = ab + b2 b = 1 + b/a would have to be true for all b. Counter-example: b = 2; a = 3 b(ab) = 2(3)(2) = 12 = ab2 = (4)(3) ab + b2 = (2)(3) + (2) = 10 but 10 does not = 12. Contradiction. So it cannot be the case that b = 1 + b/a is true for all b and, therefore, b*ab does not = ab + b2

Related questions

(a-b)2 = (a-b)(a-b). You have to multiply each term in the left monomial by each term in the right monomial: a2 - ab - ab + b2 = a2 - 2ab + b2.

It means you multiply the binomial by itself. Multiplying polynomials requires multiplying every term of the first with every term of the second. For example, (a+b)2 = a2 + ab + ba + b2 = a2 + 2ab + b2.It means you multiply the binomial by itself. Multiplying polynomials requires multiplying every term of the first with every term of the second. For example, (a+b)2 = a2 + ab + ba + b2 = a2 + 2ab + b2.It means you multiply the binomial by itself. Multiplying polynomials requires multiplying every term of the first with every term of the second. For example, (a+b)2 = a2 + ab + ba + b2 = a2 + 2ab + b2.It means you multiply the binomial by itself. Multiplying polynomials requires multiplying every term of the first with every term of the second. For example, (a+b)2 = a2 + ab + ba + b2 = a2 + 2ab + b2.

When applying distributive property to solve an equation, you multiply each term by term. For instance: a(b + c) = ab + ac

It is an expression and a term that are of equal value

Steps in getting the square of trinomial:1. Square the first term.2. Square the second term.3. Square the last term.4. Multiply the first and second term, then, square them.5. Multiply the second and third term, then, square them.6. Lastly, multiply the first and last term, then, square them.Examples:(a+b+c)^21st step: a^22nd step: b^23rd step: c^24th step: ab^25th step: bc^26th step: ac^2Then the answer will be, a^2+b^2+c^2+ab^2+bc^2+ac^2.Hope this will help you in your assignment!

Steps in getting the square of trinomial: 1. Square the first term. 2. Square the second term. 3. Square the last term. 4. Multiply the first and second term, then, square them. 5. Multiply the second and third term, then, square them. 6. Lastly, multiply the first and last term, then, square them. Examples: (a+b+c)^2 1st step: a^2 2nd step: b^2 3rd step: c^2 4th step: ab^2 5th step: bc^2 6th step: ac^2 Then the answer will be, a^2+b^2+c^2+ab^2+bc^2+ac^2. Hope this will help you in your assignment!

If you want to multiply the monomial by the polynomial, yes. In that case, you have to multiply the monomial by every term of the polynomial. For example: a (b + c + d) = ab + ac + ad More generally, when you multiply together two polynomials, you have to multiply each term in one polynomial by each term of the other polynomial; for example: (a + b)(c + d) = ac + ad + bc + bd All this can be derived from the distributive property (just apply the distributive property repeatedly).

You represent a generic trinomial with some letters, then just carry out the desired operations. The general rule to multiply polynomials is that each term in one polynomial must be multiplied by each term in the other polynomial. For example, to multiply a trinomial by itself - i.e., square it - you get: (a + b + c) (a + b + c) = a2 + ab + ac + ab + b2 + bc + ac + bc + c2 Next, you can group similar terms; well, I'll leave that to you.

false

What does high j01 ab

German

The only term I know of is AB (AB+ or AB-)